Histiocytic Sarcoma Following B-Lymphoblastic Leukemia/Lymphoma: Two Clonally Related Neoplasms Derived From a Common Precursor With Evidence of IGH-MYC and IGK Gene Rearrangements. Issue 4 (7th June 2019) - Geyer, Julia T; Yigit, Nuri; Miyaguchi, Ayako; Cheng, Shuhua; Casano, Joseph; Mathew, Susan; Desai, Pinkal; Gergis, Usama; Tam, Wayne
Abstract: Objectives: Rare cases of clonally related histiocytic sarcoma (HS) following B-lymphoblastic leukemia/lymphoma (B-ALL/LBL) have been reported to date. Methods: We present a patient with HS, which appeared as a breast mass 12 months after the initial diagnosis of B-ALL. Results: Both HS and the B-ALL shared IGH-MYC and IGK gene rearrangements. Next-generation sequencing and whole-exome sequencing (WES) studies detected 35 common mutations, as well as mutations unique to B-ALL (16) and HS (15), including BRAF D594G. The patient achieved complete remission of B-ALL, but HS failed to respond to many cycles of intensive chemotherapy regimens. A partial response was achieved with sorafenib, a BRAF -targeted therapy. Conclusions: To our knowledge, this is the first study to demonstrate by WES that clonally related B-ALL and HS arise through divergent evolution from a common precursor. We present our findings together with a discussion of the previously reported cases of HS in patients with B-ALL.